Current closed-loop control and field orientation analysis of an induction motor in six-step operation for railway applications - Fang, Xiaochun; Tian, Zhongbei; Li, Hua; Yang, Zhongping; Lin, Fei; Hillmansen, Stuart (IET power electronics, 2019)
In railway traction drive systems, six-step operation is widely used for motors in a flux-weakening region. Traditional vector control algorithms in six-step operation cannot work effectively due to the limitation of a single degree of freedom. This study analyses the dq current coupling relationship when the voltage amplitude is limited and applies a current closed-loop control strategy in six-step operation. This study proposes a proper switching control strategy to achieve a dual-mode control for induction motors in a full-speed region. The accuracy of field orientation is affected by changes in motor parameters and plays a key role in current control precision. This study analyses the effect of field orientation error on motor six-step operation. It is found that the proposed current closed-loop control strategy can correct the field orientation error and guarantee the motor current to track the reference precisely. A case study of a 5.5 kW experimental platform is presented to validate the control schemes.